Neck Kinematics in Rear-End Impacts - King H Yang; Albert L King (Pain Research and Management)
The purpose of this study was to document the kinematics of the neck during low-speed rear-end impacts. In a series of experiments reported by Deng et al (2000), a pneumatically driven mini-sled was used to study cervical spine motion using six cadavers instrumented with metallic markers at each cervical level, a 9-accelerometer mount on the head, and a tri-axial accelerometers on the thorax. A 250-Hz x-ray system was used to record marker motion while acceleration data were digitized at 10,000 Hz. Results show that, in the global coordinate system, the head and all cervical vertebrae were primarily in extension during the entire period of x-ray data collection. In local coordinate systems, upper cervical segments were initially in relative flexion while lower segments were in extension. Facet joint capsular stretch ranged from 17 to 97%. In the vertical direction, the head and T1 accelerated upward almost instantaneously after impact initiation while there was delay for the head in the horizontal direction. This combination was the result of a force vector which was pointed in the forward and upward direction to generate an extension moment. Upward ramping of the torso was larger in tests with a 20-deg seatback angle. The study concluded that the kinematics of the neck is rather complicated and greatly influenced by the large rotations of the thoracic spine. Significant posterior shear deformation was found, as evidenced by the large facet capsular stretch. Although the neck forms a 'mild' S-shaped curve during whiplash, using its shape as an injury mechanism can be misleading because the source of pain is likely to be located in the facet capsules.